PELATIHAN INOVASI MEDIA AJAR INTERAKTIF UNTUK PEMBELAJARAN PERKALIAN SEDERHANA DI SEKOLAH DASAR - Baroroh Ma'Arif, Iin; Bahtiar, Yuyun; Choirun Nisak Nur, Luluk; Afidah, Nurul; Wulan Agustina, Ulfa (ABIDUMASY, 2024)
Innovations in teaching media are essential for improving the quality of learning, especially in basic mathematical concepts such as multiplication. This article discusses community service activities in the form of training in creating interactive teaching media for simple multiplication learning. The training is aimed at primary school teachers in Rayung Village, Kepohrejo Village, Kudu District, Jombang Regency with the aim of improving their skills in creating technology-based learning media. The method used in this training is Participatory Action Research (PAR). The results of the activity showed that the participants were able to create and use technology-based interactive teaching media well, and were able to increase students' interest and understanding of multiplication materials. In conclusion, the training is effective in providing teachers with new skills and potentially improving the quality of learning in primary schools.